PENGARUH LABA PERUSAHAAN TERHADAP HARGA SAHAM PADA PT. BANK RAKYAT INDONESIA TBK. TAHUN 2016-2023 - Dumanauw, Ecclesia Natalia; Nurzahrani, Siti Fathiyyah; Gandi, Georgiana Charisima; Manurung, Elizabeth Tiur (Jurnal Akuntansi Kompetif, 2025)
This study analyzes the effect of profit on the stock price of PT Bank Rakyat Indonesia Tbk. The author uses a quantitative approach through linear regression analysis to test the relationship between company profit as an independent variable and stock price as a dependent variable. The data analyzed covers the period 2016 to 2023. Keyword: PT. Bank Rakyat Indonesia Tbk, Profit, Stock Price, Linear Regression Analysis, Financial Performance.